WUJUD WA MUSAHAMAH AS-SYAKHSHIYYAH AL-ADABIYYAH AL- ARABIYYAH FI AS-SUDAN - Aulia Rahman Alphasiri; Sutaman Sutaman; Penny Respati Yurisa (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
Literature is a form of culture in a particular region that is certainly different in every other region. In its spread, Arab literature cannot be separated from various aspects of each figure who spreads it. The influence and development of Arab literature itself are diverse. The purpose of this research is to understand the form of Arab literature development and its influence, especially in the Sudanese region. This study uses a qualitative approach that uses library research type. Data sources include articles, books, and literary studies in the Sudanese region. Data collection techniques in the existing text adhere to documentation analysis data with Miles and Huberman's model method through three stages: data reduction, data presentation and verification. The findings of this research show that the existence of Arabic literature in Sudan is not only geographically widespread in regions, but also developed through the contributions of writers whose works were deeply influenced by the country’s political and social dynamics. Figures such as Abdul Rahman al-Mahdi and Sayyid Ali Mirghani played significant roles in shaping the narrative of Arabic literature in Sudan. Abdul Rahman al-Mahdi was known as a revolutionary poet who raised themes of African identity, colonialism, and human struggle, while Sayyid Ali Mirghani depicted the social and cultural realities of local communities, especially through the use of dialect and rural Sudanese settings in his writings. Arabic literature in Sudan does not stand in isolation; rather, it evolved as a response to the country’s complex socio-political and religious conditions